Effect Of The Combination of Concentration of Naphtalene Acetic Acid (NAA) and Kinetin On The Growth of Fig Plants (Ficus carica L.) of the Green Jordan Variety in Vitro - Rusmana Putri, Devina Aulya; Komariah, Ai; Romiyadi, Romiyadi (Jurnal Agrosci, 2025)
Background. The fig plant is one of the plantation commodities that experiences a decline in production every year. The cause of the decline in fig production is the low multiplication of fig plants due to less-than-optimal plant cultivation. Fig plants have high economic value, where market demand is increasing, but production of fig plants is decreasing. Therefore, efforts are needed to increase productivity, one of which is the use of in vitro propagation techniques with the addition of NAA and Kinetin growth regulators. Aims. This research aims to investigate the growth response to the combination of Naphthalene Acetic Acid (NAA) and Kinetin concentrations on the growth of fig (Ficus carica L.), specifically the Green Jordan variety, in vitro. Methods. This experiment was carried out at the Tissue Culture Laboratory of the Regional Technical Implementation Unit, Horticulture Seed Center, Hegarmanah, Jatinangor District, Sumedang Regency, West Java. Conducted from March to May 2024, the experiment employed a Simple Randomized Environmental Design (SRE) consisting of 5 treatment combinations, repeated 4 times, resulting in 20 experimental units. A = (0 mg L-1 NAA + 4 mg L-1 Kinetin ), B = (0.5 mg L-1 NAA +3 mg L-1 Kinetin ), C = 1 mg L-1 NAA +2 mg L-1 Kinetin, D = (1.5 mg L-1 NAA + 1 mg L-1 Kinetin ), E = (2 mg L-1 NAA + 0 mg L-1 Kinetin ), Observational data were analyzed using the F test and if there is an effect followed by Duncan's Multiple Range Test at the 5% level. Conclusion. The results showed that the combination concentration (4 mg L-1 Kinetin) had a better effect on the percentage of leaves.